An optimisation model for the warehouse design and planning problem - Geraldes, Carla A.S. (2014)
In spite of the importance of warehouses in the field of the supply chain management, there is not a single decision model that integrates all the decisions that concerns the warehouse design and planning problem. In this paper we discuss a mathematical programming model aiming to support some warehouse management and inventory decisions. Our aim is to address the complexity related to the modeling of the warehouse design and planning problem. In particular an optimisation model is presented to capture the trade-offs among both inventory and warehouse costs in order to achieve global optimal design satisfying throughput requirements.